Optimizing Supply Chains Through Technology and Computational Modeling - Capulong, Alyssa Jean; Shah, Nisha (Etunas Sukses Sistem, 2025)
In the era of rapid globalization, optimizing supply chains has become essential for enhancing operational efficiency and competitiveness. This study investigates the role of technology and computational modeling in improving supply chain performance in the context of Myanmar, a developing economy with unique logistical and infrastructural challenges. By integrating advanced technologies such as IoT, data analytics, and simulation-based modeling, the research evaluates their impact on demand forecasting, inventory management, and transportation planning. A case study approach involving key sectors such as agriculture and manufacturing was employed to assess real-world applicability. Results indicate significant improvements in supply chain responsiveness, cost reduction, and decision-making accuracy. This paper contributes to the growing body of knowledge by providing insights into how emerging technologies can be effectively applied in developing countries to overcome supply chain inefficiencies. The findings also highlight the importance of tailored technological adoption strategies that consider local socio-economic and infrastructural conditions.